Analisis Pengelolaan Limbah Medis Padat Puskesmas Di Kabupaten Siak - Nursamsi, Nursamsi; Thamrin, Thamrin; Efizon, Deni (Universitas Riau, 2017)
Clinics’ solid medical waste at Siak Regency was not been carry out well. Based on the data at environment healt division of Siak health department, the volume of solid medical waste that produced was 0,74 kg/bed/day goods waste of patient treatments, 0,167 kg/patients/day waste of stay room, 0,071 kg/patient/day waste of delivery rooms and ICU rooms, and 0,004 kg/patients/day waste of polyclinic. The total of clinics’ solid medical waste at Siak Regency was 1,62 kg/day. There were 70% officers who responsible in managing the clinics’ solid medical waste did not act based on the rule, which is KEPMENKES RI No. 1428/MENKES/SK/XII/2006, 80% officers did not have knowledge about solid medical waste, 70% officers were irresponsive and 4 incinerators ini 4 clinics (Perawang, Kandis, Bunga Raya, and Mampura Clinics) were out of order. This research was conducted to analyze the officers action in managing the clinics’ solid medical waste. The population of this research was all waste labor manager and the sample was 66 waste labor manager. The data analysis was done in Univariat, Eksploratif and Multivariate.The finding shows that the officers’ act reduced to 66.7% the officers’ knowledge about clinics’ solid medical waste reduced to 59,1%, the irresponsive behaviour reduced 62,1%, and the waste facility was 72,7%. Based ont the multivariat test, it can be concluded that the officers who has irresponsive behaviour will did 14,2 times bad action in managing the clinics’ solid medical waste compared to positive action that controlled by knowledge variabel. The most impact of clinics’ solid medical waste management in 2016 was pruritis that was 52,33% and the least was get stabbed that was 3,7%.